CTGF promotes osteosarcoma angiogenesis by regulating miR-543/angiopoietin 2 signaling. (10th April 2017) - Wang, Li-Hong; Tsai, Hsiao-Chi; Cheng, Yu-Che; Lin, Chih-Yang; Huang, Yuan-Li; Tsai, Chun-Hao; Xu, Guo-Hong; Wang, Shih-Wei; Fong, Yi-Chin; Tang, Chih-Hsin
Abstract: Osteosarcoma is the most common primary solid tumor of bone. It has a high metastatic potential and occurs predominantly in adolescents and young adults. Angiopoietin 2 (Angpt2) is a key regulator in tumor angiogenesis, facilitating tumor growth and metastasis. Connective tissue growth factor (CTGF, also known as CCN2), is a cysteine-rich protein that has been reported to promote metastasis of osteosarcoma. However, the effect of CTGF on Angpt2 regulation and angiogenesis in human osteosarcoma remains largely unknown. We found that overexpression of CTGF in osteosarcoma cells increased Angpt2 production and induced angiogenesis, in vitro and in vivo . Our findings demonstrate that CTGF-enhanced Angpt2 expression and angiogenesis is mediated by the phospholipase C (PLC)/protein kinase C (PKCδ) signaling pathway. Moreover, endogenous microRNA-543 (miR-543) expression was negatively regulated by CTGF via the PLC/PKCδ pathway. We also provide evidence showing clinical significance between CTGF, Angpt2, and miR-543 as well as tumor staging in human osteosarcoma tissue. CTGF may serve as a therapeutic target in the process of osteosarcoma metastasis and angiogenesis. Highlights: CTGF increases Angpt2 in osteosarcoma. Silencing CTGF expression suppresses tumor-induced angiogenesis in vivo . Clinical importance of CTGF, Angpt2, and miR-543 in osteosarcoma patients.